PENGEMBANGAN INSTRUMEN PENGUKURAN TINGKAT PERKEMBANGAN ANAK USIA DINI (PAUD) - I Wayan Gunartha; Badrun Kartowagiran; Siti Partini Suardiman (LP3M Universitas PGRI Mahadewa Indonesia, 2019)
This study aims to: (1) develop instrument for measuring the level of early childhood development (kindergarten group B), and (2) assess the quality of developed instrument. This study is a kind of research and development. The research subject was the students of kindergarten group B. The developed instrument was in the form of questionnaires. Instrument testing was carried out in three stages with the number of subjects increased on each stage. The validity analysis of the questionnaire used cofirmatory factor analysis (CFA). The reliability estimation of the questionnaire used the CFA by calculating the composite reliability. The results of the study are in the form of instruments for measuring the level of early childhood development, which consists of an instrument to measure religious morality, social-emotional, language, cognitive, and physical-motoric development. Based on field study, all instruments have good fit model, construct validity, and reliability that meet the academic requirements.